PENDAPATAN DAN NILAI TAMBAH AGROINDUSTRI TEMPE DI KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Viona Pramayang; Dwi Haryono; Ktut Murniati (Lampung University, 2020)
This study aims to analyze the level of income and added value of tempe agroindustry. This study uses a case study method. The research location is chosen purposively in Punggur Subdistrict, Central Lampung Regency, with the consideration that Punggur Subdistrict has the highest number of tempe producers in Central Lampung Regency. The samples were chosen by accidental sampling method in three villages. The number of respondents are 42 respondents. The data used in this study are primary and secondary data. The results showed that the tempe agroindustry in Punggur Subdistrict, Central Lampung Regency was profitable and feasible because of R/C > 1 and positive added value.Key words: added value, agroindustry, income, tempe